On the assessment of fatigue life of marine diesel engine crankshafts. (October 2015) - Fonte, M.; Duarte, P.; Anes, V.; Freitas, M.; Reis, L.
Highlights: Marine diesel engine crankshafts and its design and manufacturing. Assessment of fatigue life of marine diesel engine crankshafts. Failure mode analysis of marine diesel crankshafts. Recommendations to improve the lifetime of marine crankshafts. Abstract: The fatigue strength and its correct assessment play an important role in design and maintenance of marine crankshafts to obtain operational safety and reliability. Crankshafts are under alternating bending on crankpins and rotating bending combined with torsion on main journals, which mostly are responsible for fatigue failure. The commercial management success substantially depends on the main engine in service and of its design crankshaft, in particular. The crankshaft design strictly follows the rules of classification societies. The present study provides an overview on the assessment of fatigue life of marine engine crankshafts and its maintenance taking into account the design improving in the last decades, considering that accurate estimation of fatigue life is very important to ensure safety of components and its reliability. An example of a semi-built crankshaft failure is also presented and the probable root case of damage, and at the end some final remarks are presented.